Autonomic Nervous System Function After a Skin-to-Skin Contact Intervention in Infants With Congenital Heart Disease. Issue 5 (September 2017) - Harrison, Tondi M.; Brown, Roger
Abstract : Background: Infants with complex congenital heart disease (CCHD) demonstrate impaired autonomic nervous system (ANS) regulation, which may contribute to commonly observed impairments in feeding, growth, and development. Close mother-infant physical contact improves ANS function in other high-risk infant populations. Objective: Our purposes were to examine feasibility of a 2-week daily skin-to-skin contact (SSC) intervention and to describe change in ANS function in response to the intervention. Methods: Feasibility was assessed by recruitment and retention rates, safety, and acceptability. Autonomic nervous system function was measured with linear and nonlinear measures of heart rate variability (HRV) during a feeding before the 14-day SSC intervention and 3 times during a 4-week follow-up. Results: Recruitment rate was 72%; retention rate was 55.5%. Mothers were universally positive about SSC. Ten mothers and infants completed a daily mean of 77.05 minutes of SSC during the 14-day intervention with no adverse events. Baseline high-frequency HRV, reactivity to challenge, and recovery after challenge improved during the 6-week study. Nonlinear measures demonstrated abnormally high sympathetic activity, especially after feeding, in most infants. Conclusions: Skin-to-skin contact is feasible in infants with CCHD. Linear measures of HRV suggested improvements in ANS function with this intervention. This article is one of the first to describe nonlinear HRV measures in infants with CCHD. Additional research is needed to identify variations in linear and nonlinear effects based on specific cardiac conditions and with varying intervention doses and timing. This low-cost, low-risk intervention has the potential to improve outcomes in infants with CCHD.